Diagnostic Advancement in Evaluating Inborn Errors of Metabolism: Past, Present and Future: A systematic review - Fatima, Nazmin; Tripathi, Shalini; Alam, Roshan; Siddiqui, Mohammed Haris; Mahdi, Abbas Ali; Sonkar, Gyanendra Kumar (International Journal of Human and Health Sciences (IJHHS), 2019)
Metabolism is a delicately coordinated entity of chemical reactions. Inborn Errors of Metabolism (IEM) are rare congenital disorders that are mainly due to gene defect of enzymes or cofactors participating in a metabolic pathway or the transport of metabolites within a cell or between cells. The development of knowledge in basic sciences together with technology development in medical field has helped to better understand the molecular and biochemical basis of IEM. Environmental factors, ethnicity, race, consanguinity and genetic factors contribute to the increased prevalence of genetic disorders. The analytical methods have evolved over the years from thin layer chromatography (TLC), high performance liquid chromatography (HPLC) to tandem mass spectrometry (TMS) including gas chromatography mass spectrometry (GC/MS). Their applications for È¡7_Ø‹5_g of IEM has opened the door for screening of conditions that previously required molecular testing or another methodology that was not practical for population-based screening. Future technologies such as Matrix-assisted laser desorption/ ionization timeof- flight mass spectrometry (MALDI-TOF MS), has the potential for rapid and reliable identification of small metabolites and disease biomarkers in daily clinical laboratories, whereas DNA based screening by DNA microarrays or gene chips will allow much more improved diagnosis.These can be the boon to screening programs which will require excellent detection and follow-up services International Journal of Human and Health Sciences Vol. 03 No. 02 April’19. Page: 58-63